الاصابات الحادة لأوتار اليد - بطرس, ميشيل; يوسف, صفوان; علي, ناظم محمود (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 112 حالة من الاصابات الحادة لأوتار اليد والتي راجعت قسم الاسعاف في مشفى الاسد باللاذقية بين عامين 2002-2003 وبدراسة نسب توزع هذه الحالات حسب عدة أسس تم التوصل الى عدة نتائج منها : 1 -تشكل اصابات أوتار اليد من الاصابات الرضية العامة لليد نسبة1.9% 2 -العامل المسبب الأكثر احداثا لهذه الاصابات هو الادوات الحادة كالسكين . 3 -الأشهر الأكثر تواترا” لحدوث هذه الاصابات هي أشهر الصيف . 4 -العمر الأكثر تعرضا" للاصابة هو عمر الشباب من15-30سنة. 5-الجنس الأكثر تعرضا" للاصابة هو الجنس الذكري. وبناء على هذه النتائج التي تم التوصل اليها تم وضع عدة عدة توصيات واقتراحات من شأنها العمل على الاقلال من حدوث هذه الأذيات وتحسين نتائج معالجة هذه الحالات. The study included 112 causes of acute hand tendon injuries that were attended at the emergency ward in Alassad Hospital In Lattakia between 2002-2003. We study the distridution of these causes according to several principls, and we came up with the following results: hand tendon injuries is 1.9% of all hand injuries. the most common causing factar is sharp tools such as knives. these injuries are most frequent in Summer. youths between 15-30 years old are most affected. males are more affected than female. Based on these results, we offer some suggestions and recommendation to lessen the occurance of these injuries and improve the results of treatment.